Обліково- інформаційний базис інфраструктурної підтримки ефективної амортизаційної політики - Трачова, Дар'я Миколаївна; Трачева, Дарья Николаевна; Trachova, Daria; Левченко, Ольга Петрівна; Левченко, Ольга Петровна; Levchenko, Olha; Сахно, Людмила Анатоліївна; Сахно, Людмила Анатольевна; Sakhno, Liudmyla (My University, 2020)
UK: У статті розглянуто концептуальні підходи та вимоги до формування інфраструктурної підтримки амортизаційної політики держави і підприємства. Виокремлено ключову роль бухгалтерського обліку у формуванні масиву інформації для здійснення інфраструктурної підтримки, моніторингу і контролю амортизаційної політики. Визначено роль обліково-аналітичного забезпечення інфраструктурної підтримки амортизаційної політики підприємства. Доведено важливість комплексного підходу до формування інфраструктурної підтримки амортизації. Досліджено результати застосування подібних методичних підходів у країнах зі стрімким технологічним та економічним ростом. Розглянуто можливість застосування закордонного досвіду в частині форму-вання інфраструктурної підтримки започаткування, здійснення і контролю результатів амортиза-ційної політики. Наголошено на необхідності виконання державою стимулюючої і контролюючої функцій. RU: В статье рассмотрены концептуальные подходы и требования к формированию инфраструктурной поддержки амортизационной политики государства и предприятия. Выделена ключевая роль бухгалтерского учета в формировании массива информации для осуществления инфраструктурной поддержки, мониторинга и контроля амортизационной политики. Определена роль учетно-аналитического обеспечения инфраструктурной поддержки амортизационной политики предприятия. Доказана важность комплексного подхода к формированию инфра-структурной поддержки амортизации. Исследованы результаты применения подобных методи-ческих подходов в странах со стремительным технологическим и экономическим ростом. Рассмотрена возможность применения зарубежного опыта в части формирования инфра-структурной поддержки начала, осуществления и контроля результатов амортизационной политики. Отмечена необходимость выполнения государством стимулирующей и контролирующей функций. EN: The article considers the conceptual approaches and requirements for the formation of infrastructure support for the depreciation policy of the state and the enterprise. The key role of accounting in the formation of an array of information for the implementation of infrastructure support, monitoring and control of depreciation policy is highlighted. The role of accounting and analytical support of infrastructure support of depreciation policy of the enterprise is determined. The importance of a comprehensive approach to the formation of infrastructure support for depreciation has been proved. It depends upon development of technological progress; depreciation policy affects company’s assets and the efficiency of social components in production. The reproduction of fixed assets and depreciation policy of an enterprise is not only accounting problem. Financing timely of production performance updating does not depend on the accounting interactions of accounts. This is an issue of depreciation process methodology application. The essence of the depreciation policy is determining the necessary amounts of fixed assets for the actual reproduction. This has to form the company's accounting policies. For the formation of accounting policy we should consider thoroughly the experience of our country and foreign countries. International standards allow enterprises to apply all methods of national accounting standards, in addition to production and cumulative ones. Enterprises choose the method that best reflects the expected future profit from the operation with assets. This method is constantly used during the reporting period. Method changes take place due to changes in operating the assets or receiving future economic benefits. Formation of an effective depreciation policy is a common process accounting and technical services company. To justify the need for a radical change in existing approaches to depreciation policy was studied the dynamics of fixed assets and the amount of capital investment in agriculture. To determine the depreciation policy role in the formation of investment resources of the enterprise the structure of sources of capital investment companies Ukraine. Thus, the accounting policies application for the effective depreciation policy formation is very important. The main obstacle to the formation of real depreciation fund of a company is unaccountability and vulnerability of this expenditure. Optimal depreciation and accounting policies should be based on an integrated approach based on the specific economic conditions of enterprises. Faithfulness and timeliness of depreciation is only checked while calculating the amounts of some income taxes. The results of the application of similar methodological approaches in countries with rapid technological and economic growth are investigated. The possibility of applying foreign experience in the formation of infrastructure support for the initiation, implementation and control of the results of depreciation policy is considered. The need to fulfill a stimulating and controlling function by the state was emphasized.
Accounting and information base of infrastructure support for effective depreciation policy
Keywords: амортизація; амортизаційна політика; обліково-аналітична інформація; інфраструктурна підтримка; амортизация; амортизационная политика; учетно-аналитическая информация; инфраструктурная поддержка; depreciation; depreciation policy; accounting and analytical information; infrastructure support